Reputation Risk Management in Islamic Higher Education - Jufra, Arlita Aristianingsih; Akmal; Sulaeman, Nasrullah (Institut Agama Islam Negeri Kendari, 2025)
This research aims to analyze the role of Islamic Religious Higher Education (PTKI) governance in Southeast Sulawesi, particularly in Kendari, through the lens of reputation risk management. Employing a qualitative approach with semi-structured interviews and thematic analysis, this study investigates institutional understanding of reputation risk and its governance mechanisms. The findings reveal a significant gap: while institutional leaders prioritize